Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1155/2012/151865
|View full text |Cite
|
Sign up to set email alerts
|

Association of Perceived Stress with Stressful Life Events, Lifestyle and Sociodemographic Factors: A Large-Scale Community-Based Study Using Logistic Quantile Regression

Abstract: Objective. The present paper aimed at investigating the association between perceived stress and major life events stressors in Iranian general population. Methods. In a cross-sectional large-scale community-based study, 4583 people aged 19 and older, living in Isfahan, Iran, were investigated. Logistic quantile regression was used for modeling perceived stress, measured by GHQ questionnaire, as the bounded outcome (dependent), variable, and as a function of most important stressful life events, as the predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
2
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 66 publications
6
47
2
3
Order By: Relevance
“…Patients with lower educational status had more anxiety scores and experienced stressful events ( p = 0.03). Previous studies have revealed consistent results on the relationships between perceived stress and education level and support our findings [27]. Least educated women tend to be Type B, angry, pessimistic, depressed, and dissatisfied with their work, precluded from social support and self-esteem [28].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Patients with lower educational status had more anxiety scores and experienced stressful events ( p = 0.03). Previous studies have revealed consistent results on the relationships between perceived stress and education level and support our findings [27]. Least educated women tend to be Type B, angry, pessimistic, depressed, and dissatisfied with their work, precluded from social support and self-esteem [28].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings verify their results; however, men did not show higher depression scores and experience of stressful life events than healthy men group. This may be explained by the degree of stress and the reaction of males, which can be influenced by various factors such as greater effect of sympathetic nervous system and the hypothalamic-pituitary-adrenal axis, personal characteristics, sociodemographic, and cultural and occupational variables [27]. …”
Section: Discussionmentioning
confidence: 99%
“…Gender differences in stress reactivity have been attributed to structural inequalities in the social environment. Structural inequalities are differences in society, usually in income and education, that exist where groups such as women are systematically disadvantaged compared to men [19,36]. Finally, (4) Gender-role socialization.…”
Section: Discussionmentioning
confidence: 99%
“…6 The development of depression in later life is likely to involve multi-risk factors encompassing genetic vulnerabilities, physical illness, disability, cognitive derangements, physiological dysregulation, age-associated neurobiological changes and stressful events. [14][15][16] Personal burden and responsibilities change according to stages in life. Stressful life events might create psychological distress in older persons by eroding their sense of personal control and feelings of self-worth.…”
Section: Introductionmentioning
confidence: 99%
“…9 Studies have shown that concerns over one's own health 5,7,10 and financial hardships [11][12][13] are two major situations of perceived stress, but concern over one's own job, relationship strain with family members, and worry over family members' health, financial, work and marital problems have also been reported to be important stressors in older adults. [14][15][16] Personal burden and responsibilities change according to stages in life. Zheng and Lin observed three specific "peaks" representing different types of life events associated with stages of transitions in the life of the contemporary Chinese population.…”
Section: Introductionmentioning
confidence: 99%